Survey of financial market visualization utilizing interactive media technology - Lugmayr, Artur (2015)
© Springer International Publishing Switzerland 2015. Big Data, as well as the visualization of data is a buzzword today. This publication surveys latest trends in visualization in financial industries. A very basic framework considering the different data, interaction, user, method, and evaluation methods is presented. Following a basic review of the existing literature in financial industry visualization, the framework is described in further depths, and shades insight into the different criteria of financial visualization in e.g. the contexts of regulation, market observation, prediction of market forecasting, and visualization of statistical information. The publication rounds up with a discussion of latest trends in media technology, and how these might impact the way how financial industries adopt these into their work-practices, such as virtual currencies, crowd-funding, social media trading, crowd-sourcing, or analysis of financial news. Thus, this publication manifested as a survey article about latest interactive media technology, and how this technology is enriching financial industries in many aspects for the purpose of visualization.